Adversarial justice and victims' rights: reconceptualising the role of sexual assault victims - Iliadis, Mary (Routledge, 2020)
Introduction -- Tracing the interest in victims, victims' rights and sexual assault law reform -- Procedural justice -- Providing a check on prosecutorial decision-making -- Separate legal representation for victims under section 34 of the Sex Offenders Act 2001 (Irl) -- Victim participation through the SACVR -- The prospect of ILR for sexual assault victims within Victoria's criminal prosecution process -- Chapter 8: Concluding comments